The role of structure in manipulating PPP accountability. Issue 1 (16th January 2017) - Agyenim-Boateng, Cletus; Stafford, Anne; Stapleton, Pamela
Abstract : Purpose: The purpose of this paper is to examine the accounting and governance of public private partnerships (PPPs) that are structured as joint venture partnerships. Drawing on Giddens' structuration theory, the paper examines how human agents interact with these joint venture structures and analyses the effects on financial disclosures and public accountability for taxpayers' investments. Design/methodology/approach: The authors adopt a cross-case analysis to investigate two such PPP schemes, which form part of the UK's programme of investment in primary healthcare, known as the Local Improvement Finance Trust (LIFT) policy. The authors employ a combination of interviews and analysis of financial statements and publicly available official documents. Findings: The corporate structure of these LIFT schemes is very complicated so that the financial accounting is opaque. The implication is that the joint venture mechanism cannot be relied upon to deliver transparency of reporting. The paper argues that the LIFT structures are deliberately constructed by human agents to act as barriers to transparency about public expenditure. Practical implications: The financial reporting undermines public accountability and transparency as both are necessarily restricted. Policy makers should pay attention to not only the private sector technologies but also the manner in which structures are used to reduce transparency and consequently undermine public accountability. Originality/value: The paper provides detailed analysis from the perspective of structuration theory to show how human agents use structures to impact on financial reporting and public accountability.